(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background Antibiotic resistant bacterial nosocomial infections are a leading problem in intensive care units (ICU). Objective To study the pattern of microorganism and bacterial resistant to antibiotic in ICU of Bangabandhu sheikh Mujib Medical University of Bangladesh. Methods This retrospective study was conducted in ICU of Bangabandhu Sheikh Mujib Medical University, Bangladesh from January 2010 to December 2012. Total number of samples were 448. The samples of tracheal aspirate, blood and urine for culture and sensitivity was collected from the patient admitted in ICU. Analysis of tracheal aspirate, blood and urine culture was done from hospital record. All bacteria was identified by standard microbiological methods, and their antibiotic sensitivity was performed using disk diffusion method. Results Total number of samples 448. Samples of tracheal aspirate was 159, positive culture 121(76%), most frequent identified organism was acenetobacter 45.45%, followed by pseudomonas 32.23%, proteus 11%, klebsiella 10% and E.coli 3%, samples of blood culture was 148, positive culture 22(14.86%), most frequent identified organism was pseudomonas 63.63%, followed by acenetobacter 22.72%, salmonella 4.54% and E.coli 4.54% and samples of urine culture was 141, positive culture 36 (25.53% ) most frequent identified organism was enterococcus 22.22%, followed by acenatobacter 19.44%, candida16.66%, klebsiella 13.88% and E.coli 13.88%. Drug resistant organism of tracheal aspirate was 12(20.33%) in 2010, 2(20%) in 2011 and 13(25%) in 2012. only collistin sensitive organism identified was 28(23.14%). Conclusion From this study we concluded that most common site of infection was respiratory tract and most prevailing organism was acinetobacter & pseudomonas and antibiotic resistant infection is increasing and at present around one fourth organisms were resistant to all antibiotics. DOI: http://dx.doi.org/10.3329/jbsa.v26i1.19811 Journal of Bangladesh Society of Anaesthesiologists 2013; 26(1): 20-26